Epistemology Of Legal Studies: Research Method Characteristics of Theoretical Law Bearers in Indonesia - WARDIONO, KELIK; DIMYATI, KHUDZAIFAH; YUSPIN, WARDAH; NUGRAHA, TASYHA PANJI; BUDIONO, ARIEF; ROCHMAN, SAEPUL (Journal of Ecohumanism, 2024)
Doctorate students of legal studies programs in Indonesia use various research methods. This paper aims to analyze research methods patterns used by doctorate students of legal studies in six Indonesian universities. The authors analyzed dissertations from the Doctorate Program of Legal Studies in the following universities: Universitas Indonesia (Depok, West Java), Universitas Padjajaran (Bandung, West Java Province), Universitas Sumatera Utara (Medan, North Sumatra Province), Universitas Airlangga (Surabaya, East Java Province), Universitas Diponegoro (Semarang, Central Java Province), and Universitas Hasanuddin (Makassar, South Sulawesi Province). This philosophical method research used secondary data obtained using the literature review method in the form of dissertations from six universities that establish legal studies doctorate programs. Results showed that there are three patterns of epistemology used by doctorate program students of legal studies in Indonesia, namely those that are based on the doctrinal approach, those based on the non-doctrinal approach, and those based on the combined approach between the doctrinal and the non-doctrinal approaches. In this research, some dissertations with the epistemological pattern were also found that are is based on theoretical assumptions sourced from the teachings of the positivistic legal philosophy school of thought as taught by Austin and Kelsen.